Potential Cross-Reactive Immunity to COVID-19 Infection in Individuals With Laboratory-Confirmed MERS-CoV Infection: A National Retrospective Cohort Study From Saudi Arabia - Khan, Anas A.; Alahmari, Ahmed A.; Almuzaini, Yasir; Alamri, Fahad; Alsofayan, Yousef Mohammad; Aburas, Alhanouf; Al-Muhsen, Saleh; Van Kerkhove, Maria; Yezli, Saber; Ciottone, Gregory R.; Assiri, Abdullah M.; Jokhdar, Hani A. (Frontiers in Immunology, 2021)
Background: A growing number of experiments have suggested potential cross-reactive immunity between severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and previous human coronaviruses. We conducted the present retrospective cohort study to investigate the relationship between previous Middle East respiratory syndrome-coronavirus (MERS-CoV) infection and the risk of SARS-CoV-2 infection as well as the relationship between previous MERS-CoV and COVID-19-related hospitalization and mortality. Methods: Starting in March 2020, we prospectively followed two groups of individuals who tested negative for COVID-19 infection. The first group had a previously confirmed MERS-CoV infection, which was compared to a control group of MERS-negative individuals. The studied cohort was then followed until November 2020 to track evidence of contracting COVID-19 infection. Findings: A total of 82 (24%) MERS-positive and 260 (31%) MERS-negative individuals had COVID-19 infection. Patients in the MERS-positive group had a lower risk of COVID-19 infection than those in the MERS-negative group (Risk ratio [RR] 0.696, 95% confidence interval [CI] 0.522-0.929; p =0.014). The risk of COVID-19-related hospitalization in the MERS-positive group was significantly higher (RR 4.036, 95% CI 1.705-9.555; p =0.002). The case fatality rate (CFR) from COVID-19 was 4.9% in the MERS-positive group and 1.2% in the MERS-negative group (p =0.038). The MERS-positive group had a higher risk of death than the MERS-negative group (RR 6.222, 95% CI 1.342-28.839; p =0.019). However, the risk of mortality was similar between the two groups when death was adjusted for age (p =0.068) and age and sex (p =0.057). After controlling for all the independent variables, only healthcare worker occupation and >1 comorbidity were independent predictors of SARS-CoV-2 infection. Interpretation: Individuals with previous MERS-CoV infection can exhibit a cross-reactive immune response to SARS-CoV-2 infection. Our study demonstrated that patients with MERS-CoV infection had higher risks of COVID-19-related hospitalization and death than MERS-negative individuals.